Macrolensing signatures of large-scale violations of the weak energy condition - Safonova, Margarita (2001)
We present a set of simulations of the macrolensing effects produced by large-scale cosmological violations of the energy conditions. These simulations show how the appearance of a background field of galaxies is affected when lensed by a region with an energy density equivalent to a negative mass ranging from 1012 to 1017 |M |. We compare with the macrolensing results of equal amounts of positive mass, and show that, contrary to the usual case where tangential arc-like structures are expected, there appear radial arcs — runaway filaments — and a central void. These results make the cosmological macrolensing produced by space–time domains where the weak energy conditions are violated, observationally distinguishable from standard regions. Whether large domains with negative energy density indeed exist in the universe can now be decided by future observations of deep fields.